The Sclera - Sainz de la Maza, Maite; Tauber, Joseph; Foster, C. Stephen (Springer New York : Imprint: Springer, 2012)
The Sclera is the definitive text on the diagnosis and treatment of scleral diseases, with in-depth chapters on non-infectious scleritis, infectious sclertitis, non-inflammatory diseases of the sclera, and systemic implications of scleral disease. Basic physiology, anatomy, and biochemistry are addressed as well. Written for the ophthalmologist, the revised and updated new edition of The Sclera contains the most current information available on newer characterizations of the composition of the sclera, immune derangements of it, and success in medical and surgical treatment of the inflammatory diseases of the sclera.